Effects of obesity on liver cytochromes P450 in various animal models - Tománková, Veronika; Anzenbacher, Pavel; Anzenbacherová, Eva (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2017)
The prevalence of obesity and other obesity-related diseases is increasing worldwide. Obesity is a disease characterized by increased body weight, or a condition resulting from excessive accumulation of body fat. Due to increased body fat deposits, obesity has also been associated with increased mortality resulting from higher incidence rates of hypertension, diabetes, or various types of cancer, such as breast, colorectal, cervical and prostate cancer. Physiological changes associated with obesity are likely to result in altered drug biotransformation. The main enzymes enabling the oxidative biotransformation of most drugs are cytochromes P450 (CYPs). The review summarizes how pathophysiological factors, especially obesity, affect properties (e.g. enzyme activity, protein expression, gene expression) of CYP enzymes in various experimental models of human obesity. Results reported by various authors suggest that obesity is associated with a decrease of CYP activities (except for the CYP2C and CYP2E1 enzymes). The only exception is mouse obesity induced by monosodium glutamate (administered to newborn mice) as it usually leads to increased CYP expression. Selecting an animal model that is as close as possible to the properties of human obesity is of paramount importance.
Keywords: Disease Models, Animal; Obesity; myši; Animals; obezita; Adipose Tissue; Cytochrome P-450 Enzyme System; zvířata; Mice; modely nemocí na zvířatech; systém (enzymů) cytochromů P-450; tuková tkáň; jaterní mikrozomy; Microsomes, Liver